Solving manufacturing problems for L-carnitine-L-tartrate to improve the likelihood of successful product scale-up - Badawi Aliaa A.; Hegazy Mahmoud M.; Louis Dina; Eldegwy Mohammed A. (Acta Pharmaceutica)
L-carnitine-L-tartrate, a non-essential amino acid, is hygroscopic. This causes a problem in tablet production due to pronounced adhesion of tablets to punches. A 33 full factorial design was adopted to suggest a tablet formulation. Three adsorbents were suggested (Aerosil 200, Aerosil R972, talc) to reduce stickiness at three concentrations (1, 3 and 5 %), and three fillers (mannitol, Avicel PH 101, Dibasic calcium phosphate) were chosen to prepare 27 formulations. Micromeritic properties of formulations were studied, and tablets were prepared by wet granulation. Absence of picking, sticking or capping, recording of sufficient hardness, acceptable friability and tablet ejection force indicated formulation success. The resulting formulation prepared using Avicel PH 101 and 1 % Aerosil 200 was submitted to further investigation in order to choose the most suitable compression conditions using a 33 full factorial design. Variables included compression force, tableting rate and magnesium stearate (lubricant) concentration. The formulation prepared at compression force of 25 kN, using 2 % magnesium stearate, at a production rate of 30 tablets/ minute, was found to be the most appropriate scale up candidate.